Процесна модель управління технологічною підготовкою виробництва в середовищі інтегрованих автоматизованих систем - Трейтяк, Вячеслав Віталійович (НТУ "ХПІ", 2015)
Розглядається процесна модель технологічної підготовки виробництва з погляду реінжинірингу існуючих виробничих процесів на підприємстві, введення ключових показників діяльності в модель, яка розробляється з метою подальшого контролю ефективності системи технологічної підготовки виробництва в рамках моделювання за різними сценаріями. Представлено розроблені організаційні моделі технологічної підготовки виробництва. Результати досліджень можуть бути використані при розробці інформаційних систем та технологій автоматизації основних етапів життєвого циклу наукоємного виробу.

The process’s model of technological preproduction is examined coming from reengineering of existent productive processes on an enterprise, introduction of key performance indicators to the model that is developed with the purpose further control of efficiency system of technological preproduction within the framework of design on different scenarios. The worked out algorithm of development of process's model technological prepro-duction is presented. Principles of design at description of process technological preproduction are certain. A research result is a model organizational model of technological preproduction that can be used on different machine-building enterprises as guidance on a management by the processes of technological preproduction. The worked out organizational models of technological preproduction are presented. The results of researches can be drawn on at development of the informative systems and technologies of automation of the basic stages of life cycle of difficult technical detail.
Process’s case frame technological preproduction in the delirium of the integrated automated systems
Keywords: машинобудівні підприємства; організаційна модель; імітаційне моделювання; управління виробничими процесами; technological preproduction; organizational model; imitation design; management by productive processes